Importance of Religion for the Survival and Development of an Ethnic Group of People - Vilmane, Nora (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2012)
The research deals with the emigration of Latvians to Brazil in the 19th and 20th centuries, its motives and goals. It contains the analysis of religious traditions and activities in the Latvian colony Vārpa and their role in the development of the community of Latvian diaspora. A unique phenomenon – activities of Latvian missionaries – has been examined and evaluated in the context of facilitating the inhabitants’ spiritual development in remote regions of Brazil and Bolivia. During several expeditions (1999, 2001, 2009) the author has studied the basic values and way of life of the Latvian diaspora in Brazil in the 21st century. It has to be concluded that among Latvians both the ethnic and religious identity is still strong. The interaction of these two phenomena has ensured qualitative development of several generations of Latvians as well as their successful integration in the local multicultural society.